PENENTUAN BILANGAN PEROKSIDA MINYAK RBD (REFINED BLEACHED DEODORIZED) OLEIN PT. PHPO DENGAN METODE TITRASI IODOMETRI - Yeniza; Asmara, Anjar Purba (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2019)
This study aims to determine the quality of RBD olein produced by PT. PHPO according to the peroxide number which refers to SNI 01-3741-2002. The sample used is a yellow liquid fraction obtained by fractionation of RBD palm oil or crude palm oil CPO which has undergone a refining process. The sample was analyzed using the iodometric titration method. The results of the calculation of the average peroxide number of RBD olein oil is 0.282 mg O2 / 100 g. Based on these data, Olein RBD oil meets the company quality standard and SNI 01-3741-2002.